Kathy Smith matrix method. Power walk for weight loss [videorecording (DVD)]. - Smith, Kathy, 1951- (Goldhil Entertainment, 2006)
"This is not your ordinary walking workout! My Power walk for weight loss is a new spin on my favorite exercise. I've combined the latest techniques for total body toning with walking to give you all-over results fast! Finally, you can sculpt your abs, and define your arms and shoulders, all while you walk! Plus, you'll burn more calories in less time!"--Container.